The relationship between construction sector and economic in Malaysia - Mohamad Kamal, Ghani (2017)
Construction industry plays an important roles in development of country. At the same time, economy can affect construction industry activities. So that, a research has been done to determine relationship between construction and economy in Malaysia. According to from Gross Domestic Product (GDP), annual percentage economy having an increasing and decreasing from years to years. This is also can affect the construction industry performance to development. During unstable economy phase, construction activities can be in risks, and will contribute to loss if do not have a good planning. The objective for this research is to analyse relationship between construction industry and economy in Malaysia. At the same time, some challenges in construction industry has been observed. Quantitative method been used to interpret the result. The result shows construction industry having a good relationship such as a great investment, inflation rate affect the demand in construction and materials suppliers for construction industry can increase economy. In addition, the result shows problems in Malaysian construction industry such as lack of labour, uneven revenue and expected expense of project can affect contractors, building materials and land cost variation. Construction industry also can increase percentage of Gross Domestic Product (GDP). Moreover, construction industry can increase job opportunities and at the same time, the construction industry allows exchange of foreign technology.